Evaluasi Sistem Surveilans Epidemilogi Penyakit Covid-19 Pasca Pandemi Di Puskesmas Nambo Kota Kendari - Irma, Irma; Handayani, Listy; Masluhiya AF, Swaidatul (Universitas Tribhuwana Tunggadewi, 2024)
COVID-19 has spread rapidly throughout the world that affecting the community life. The government has strictly taken health and social measures that have been imposed by all countries to decrease of COVID-19 spreading. Health care units are the forefront of dealing with health problems in the community due to COVID-19. Therefore, the role of Puskesmas in the detection, prevention and response very crucial as the health care unit in the first level. In supporting that matter, the implementation of epidemiological surveillance system can be used to monitor the trend of COVID-19 transmission from local, national and global levels in conducting early detection in the areas without virus transmission, monitoring cases in the areas with virus transmission, including vulnerable populations identification, providing epidemiological information to carry out risk assessments and to evaluate the impact of pandemic on health and social service. This study aimed to provide an overview the implementation of COVID-19 epidemiological surveillance system at the puskesmas level in Kendari City, 2021 to improve the epidemiological surveillance system quality. A descriptive qualitative with phenomenological design was carried out. The informants consisted of 2 key informants (surveillance programmer and head of puskesmas) and 1 ordinary informant, KTU of Nambo Health Center. The results showed that the implementation of COVID-19 epidemiological surveillance system at the Nambo Health Center in the aspects of data collection and dissemination have been carried out optimally, but the data analysis has not been carried out properly. The data processing and data interpretation aspects are not implemented.